CONTRIBUTION OF THE PRINCIPAL SUPERVISION AND WORK MOTIVATION ON TEACHER PERFORMANCE AT PUBLIC HIGH SCHOOL IN BARITO KUALA DISTRICT - Rahmatullah, Muhammad; Saleh, Muhammad; Metroyadi, Metroyadi (Journal of K6, Education and Management, 2019)
The purpose of the research is to know the Principal?s supervision contribution and work motivation toward the teachers performance at public of Senior High School at Barito Kuala, District. The research population is publicteachers at public  Senior High School in Barito Kuala, District, as much as 227 teachers. And, to take a sample it?s used Probability Sampling with Simple Random Sampling technique by determining sample to each school in a proportional manner and found  as much as 145 teachers.  For data collection is conducted by questionnaire. And the questionnaire validity trial is conducted by corrected item -  Total correlation. Reliability trial is using Cronbach?s Alpha (a). Data Analysis is taking simple regression and double technique. The data?s outcomes are: (1) significantly, there is  the Principal?s supervision contribution toward teachers performance at Senior High School in Barito Kuala, with determination value 66,1%; (2) There is a work motivation contribution towards teachers performance at public of Senior High School in Barito Kuala, significantly with determination value 65,6%; (3) And so, with significantly there is a Principal?s supervision contribution and work motivation toward teachers performance at Public of Senior High School in Barito Kuala District, in the manner of determination value 74,8%